Aaron jako nauczyciel świadectw (Syr 45,17) - Pudełko, Jolanta Judyta (Verbum Vitae, 2015)
In the Greek version of the Book of Sirach the term martu,rion (testimony) appears twice. Besides Sir 36:14, the word appears also in the Praise of the Ancestors in reference to Aaron (Sir 45:17). Moses’ brother is described there as the one who is to teach Jacob the testimonies (dida,xai to.n Iakwb ta. martu,ria), an expression that is missing from all other Biblical texts referring to Aaron. Therefore, the context of this expression, i.e. the praise of Aaron in Sir 45:6-22, is first analyzed and then various textual versions of Sir 45:17 are compared. Understanding the meaning of the term testimony in this context is made possible by the analysis of this word in other Biblical contexts, both those connected with the history of Aaron and the Sinai covenant as well as other, unrelated texts. Finally, the expression referring to Aaron is placed within the times of Sirach and those of the translator of the Greek version of the book. The key to understanding Sir 45:17 is found in the function and significance of the post-exile high priest. He is – as understood in the Book of Sirach – the only mediator between God and his people, and thus becomes the living symbol of covenant, responsible for transmitting testimonies: the Word of God, the content and requirements implied by the covenant made with God.